-7/6x-2-5/6x-7=3

Simple and best practice solution for -7/6x-2-5/6x-7=3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7/6x-2-5/6x-7=3 equation:


x in (-oo:+oo)

(-7/6)*x-((5/6)*x)-7-2 = 3 // - 3

(-7/6)*x-((5/6)*x)-7-3-2 = 0

(-7/6)*x+(-5/6)*x-7-3-2 = 0

-2*x-12 = 0 // + 12

-2*x = 12 // : -2

x = 12/(-2)

x = -6

x = -6

See similar equations:

| 3-4x-3/4 | | (X+6)+(3x+5)= | | 500-2*x=20000 | | 3/12x6= | | 0.04(2c-36)=-0.8(c-7) | | 3z^5/z^5 | | 12+3x=90 | | -6x-15+8x+21=4 | | 18+6w=2w+20 | | J-6j-40=0 | | 2n+3n+7=-8 | | P=55-0.05x | | -7x-6+9x=2 | | -2.4x=0.48 | | 3(y+8)=24 | | -3x-42+10x+12=18(x+2) | | 0.8x+3.8=0.7x+2.4 | | 15n+10s=70 | | 2x+18=3+7x-5 | | 7x+2w=180 | | 14=1/3x-5 | | 2/3x=-7.5 | | 14=5x-1/3 | | 2o+9b=38 | | -8x+14+10x-17=6 | | W-5w^2+6=0 | | 4/7x-28 | | -2.2c=17.6 | | 0.50y+5-.75y=0 | | 6(3z-5)=204 | | 3b+17-1+b-4squared=96 | | -75/-15=-5 |

Equations solver categories